Commodity Hoarding (Ihtikar) in Surah Al-Hashr: Exploring Historical Roots and Reassessing Interpretative Perspectives - Saifullah, Ulinnuha (Sharia and Law Faculty of Sunan Kalijaga Islamic State University Yogyakarta, 2023)
Abstract: Cases of hoarding of goods still often occur even though legal instruments that prohibit hoarding have existed for a long time. Thus, efforts to prevent hoarding are not enough with legal instruments alone. Joint efforts are needed to mitigate hoarding. In this case, educating Muslims, as adherents of the majority religion in Indonesia, regarding Islamic views on the practice of hoarding needs to be presented. This paper aims to examine Islamic law regarding hoarding through the perspective of the Koran. The focus of the Qur'anic verses studied is Al-Hashr verse 7. The research method used is literature research with language, ushul fiqh, and historical approaches. The results of the study show that Islam Prohibits the act of hoarding goods needed by society because this action is contrary to the principle of economic equity. The principle of economic equity is the universal value of Surah Al-Hasyr verse 7. Hoarding which is prohibited by Islam is hoarding which is done by withholding the distribution of goods that are needed by the community, so that the price rises, to then be resold when the price has increased.Abstraks: Kasus penimbunan barang masih sering terjadi padahal instrumen hukum yang melarang penimbunan telah ada sejak lama. Dengan demikian, upaya mencegah penimbunan tidak cukup hanya dengan instrumen hukum. Perlu upaya bersama untuk memitigasi terjadinya penimbunan. Dalam hal ini edukasi umat Islam, sebagai pemeluk agama mayoritas di Indonesia, mengenai pandangan Islam terhadap praktik penimbunan perlu dihadirkan. Makalah ini bertujuan meneliti hukum Islam tentang penimbunan melalui perspektif Al-Qur’an. Fokus Ayat Al-Qur’an yang diteliti adalah surat Al-Hasyr ayat 7. Metode penelitian yang digunakan adalah penelitian pustaka dengan pendekatan bahasa, ushul fikih dan sejarah. Hasil penelitian menunjukkan bahwa perbuatan menimbun barang yang dibutuhkan oleh masyarakat dilarang oleh Islam, karena tindakan tersebut bertentangan dengan prinsip pemerataan ekonomi. Prinsip pemerataan ekonomi adalah nilai universal dari surat Al-Hasyr ayat 7. Tindakan penimbunan yang dilarang oleh Islam adalah penimbunan yang dilakukan dengan menahan distribusi barang yang dibutuhkan masyarakat, supaya harganya naik, untuk kemudian dijual kembali saat harganya telah naik.